Simulasi suis optik menggunakan teknologi MEMs - Adon, Mohamad Nazib (2006)
MEMs or known as MicroElectromechanical System is first introduced in 1980s. This technology is a combination of sensors, mechanical and electronic elements. All of them are unite in single basic material (silicon) and fabricated using a micro-fabrication system. Two micro fabrication techniques are normally used, a bulk micro-machining and surfaced micro-machining technique. The latter technique is preferred due to advanced fabrication technique and its ability to construct complex mechanical structures. In this project, a CoventorWareâ„¢ software that is based on surfaced micro-machining technique is applied. In order to obtain an optimum design, a basic two dimensional (2D) design is done to identify the actual width, length and thickness of the MEMs device. The 2D design is then converted to three dimensional (3D) design where a boundary condition analysis is done. Four types of meshing analysis are adopted in CoventorWareâ„¢ which are surfaces, tetrahedron, Manhattan brick and extruded. The meshing analysis selection is based on simulation period together with the level of analysis correctness. In order to identify the existence of any capacitance and pressure effects on the developed design, the electrostatic and electromechanical analyses are carried out. Finally, analyses on the combined solutions of electrostatic and electromechanical analyses are done for the active device application